EDUKASI KESEHATAN PRENATAL YOGA PADA IBU HAMIL TRIMESTER III DI PUSKESMAS PUTRI AYU KOTA JAMBI - Nurbaiti Nurbaiti (Jurnal Abdimas Kesehatan (JAK), 2019)
Pregnancy is a natural event experienced by a mother. During pregnancy, the mother will experience physical and mental changes. Changes that occur even provide discomfort for mothers such as back pain, aches in the legs, anxiety, and so forth. One treatment for pregnancy is exercise. pregnant women who exercise regularly, report lower levels of discomfort during the pregnancy process, and heal faster than those who do not exercise during pregnanc. For those who are active in sports, require a little intervention Sectio Caesarea (SC) and can shorten the first and second stages of labor compared with those who do not exercise. One of the sports is prenatal yoga. Putri Ayu Health Center is one of the Health Centers that has provided pregnancy exercise services but has never provided prenatal yoga services in pregnancy, on the grounds that there are no trained personnel at the Puskesmas. Community Service Activities carried out at the Putri Ayu Health Center, Jambi City, time of implementation in June 2019. The target is pregnant women, especially TM III with survey approach methods, lectures, discussions, demonstrations / simulations. The results obtained by mothers are able to understand about prenatal yoga and its benefits and can do prenatal yoga routinely. It is suggested to the puskesmas to facilitate prenatal yoga.